Herdsmen/Native Farmersâ€™ Violence in Benue State and Food Security in Nigeria - Alao, David Oladimeji; Shaibume, Benjamin; Ogunwemimo, Taiwo; Alao, Esther Monisola; Ogunwemimo, Oluwafisayo (Richtmann Publishing, 2019)
The herdsmen/farmersâ€™ violence in Benue State, Nigeria has constituted security challenges and could have contributed to food insecurity as more than 2000 lives were lost in Nigeria and over 170,000 were internally displaced in Benue state, a state tagged â€œfood Basket of Nigeriaâ€. The paper among others examined the effects of the violence on food production in Benue State and Nigeria. It was descriptive study that adopted mixed method, using quantitative and qualitative approaches by relying on secondary data. The violence was negatively significantly correlated with sorghum production alone out of ten food crops examined in Benue State (p0.05). Population growth was significantly correlated with maize production only (p=0.023); agricultural budgetary allocation was positively significantly correlated with rice production only (p=0.001). It concluded that food insecurity in Nigeria was beyond herdsmen/farmersâ€™ violence. It recommended modernization and transformation of agriculture to increase food production and government should develop political will and be proactive in confronting security challenges in an inclusive manner.